Beyond Language: A Multi-Level Framework for Integrating CALD Nurses in Global Healthcare Systems - Anggun Novia Indah Fitri; Fatma Lutfiyatus Sayyida; Indi Dwi Shofi Yanti (Interdisciplinary Journal of Ethnopsychiatric Nursing, 2025)
The integration of Culturally and Linguistically Diverse (CALD) nurses into global healthcare systems presents both strategic opportunities and complex challenges. This study systematically reviews empirical evidence on professional language acquisition and integration strategies for CALD nurses, drawing on qualitative and mixed-methods research published between 2010 and 2025. Utilizing theoretical frameworks such as Adult Learning Theory, Social Integration Theory, and Systems Theory, the analysis explores how multi-level support systems including workplace-based language programs, peer mentoring, and institutional policies shape professional outcomes. Findings reveal that successful integration is not solely dependent on individual language proficiency but is deeply influenced by organizational commitment, inclusive leadership, and culturally responsive practices. Structured interventions like clinical communication workshops and the Språkombud (“Language Advocate”) model demonstrate significant impact on enhancing communication competence, emotional well-being, and job satisfaction among CALD nurses. Furthermore, peer collaboration and institutional equity policies contribute to fostering inclusive work cultures and improving patient care outcomes. The synthesis underscores the necessity of a coordinated, multi-level framework to ensure sustainable integration, reduce workforce disparities, and enhance the quality of care in multicultural clinical settings. By aligning pedagogical, interpersonal, and policy-driven strategies, healthcare organizations can create equitable pathways for CALD nurse retention and professional growth, ultimately strengthening workforce diversity and cultural competence in healthcare delivery.